FAKTOR YANG MEMPENGARUHI DERAJAT GAGAL JANTUNG DI R. RAWAT INAP PENYAKIT DALAM RSUD KEBUMEN - Padoli .; Sari Luthfiyah; Nuryati . (JURNAL PENELITIAN KESEHATAN, 2014)
This research is analytic study with cross-sectional design that aims to analyze the factors that affect the degree of heart failure in hospitalized nap room Kebumen district hospitals. The population of this research all heart failure patients who were treated in hospital room admissions folder Kebumen, while the sample as 22 people, which is selected by quota sampling. Independent variables are factors: blood pressure, nutritional status, blood glucose levels, and smoking, while the dependent variable degrees of heart failure. Data obtained by using a question and answer questionnaires, direct measure blood pressure, body mass index, blood glucose levels, as well as secondary data and the degree of heart failure are taken and the patient's medical record. Analysis using the Spearman rank test statistical test for blood pressure variables, nutritional status, and blood glucose levels and Chi Square for smoking variables. The result: nearly half a grade 3 heart failure, nearly half of stage 2 hypertension, the majority of normal nutritional status, the majority of normal blood glucose levels, and most do not smoke. Test results showed that there were factors influence blood pressure and smoking habits of the degree of heart failure. While the factors that do not affect the degree of heart failure, namely nutritional status and blood glucose levels. Keywords: Heart failure, blood pressure, nutritional status, blood glucose, smoking